Social and structural factors increase inconsistent condom use by sex workers' one-time and regular clients in Northern Uganda. Issue 6 (3rd June 2018) - Duff, Putu; Birungi, Josephine; Dobrer, Sabina; Akello, Monika; Muzaaya, Godfrey; Shannon, Kate
ABSTRACT: While sex workers (SWs) bear the brunt of the epidemic in Uganda, there remains a dearth of empirical research on the structural drivers of HIV prevention among SWs. This study examined the drivers of inconsistent condom use by one-time and regular clients of young women SWs in Gulu, Northern Uganda. Data were drawn from the Gulu Sexual Health Study, a cross-sectional study of young SWs, aged 14 years and older (2011–2012). SWs were recruited using peer/SW-led outreach, in partnership with The AIDS Support Organization and other CBOs. Multivariable logistic regression was used to examine the correlates of inconsistent condom use by one-time and regular clients. In total, 84.5% of the 381 SWs servicing regular clients and 76.8% of the 393 SWs servicing one-time clients reported inconsistent client condom use. In multivariable analysis, physical/sexual violence by clients (AOR = 5.39; 95%CI 3.05–9.49), low sexual control by workers (measured by the validated Pulweritz scale) (AOR = 2.86; 95%CI 1.47–5.58), alcohol/drug use while working (AOR = 1.98; 95%CI 1.17–3.35) and migration to Gulu for sex work (AOR = 1.73; 95%CI 0.95–3.14) were positively correlated with inconsistent condom use by one-time clients. Correlates of inconsistent condom use by regular clients included: low sexual control by workers (AOR = 4.63; 95%CI 2.32–9.23); physical/sexual violence by clients (AOR = 3.48; 95%CI 1.85–6.53); police harassment (AOR = 2.57; 95%CI 1.17–5.65); and being a single mother (AOR = 2.07; 95%CI 1.09–3.93). Structural and interpersonal factors strongly influence inconsistent condom use by clients, with violence by clients and police, low sexual control by workers, migration and single-parenthood all linked to non-condom use. There is a need for peer-led structural interventions that improve access to occupational health and safety standards (e.g., violence prevention and alcohol/drug harm reduction policies/programming). Shifts away from the current punitive approaches towards SWs are integral to the success of such interventions, as they continue to undermine HIV prevention efforts.